Efektivitas Penerapan Model Problem Based Learning (PBL) dalam Pembelajaran Tematik Kelas V SDN 36 Pontianak Kota - Nurhatasa, Nurhatasa; Hamdani, Hamdani; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study uses a quantitative method and is a sort of descriptive research. The purpose of this study is to evaluate and describe the success of using the problem-based learning (PBL) model in thematic learning in class V of SDN 36 Pontianak Kota as measured by 4 indicators: management of learning implementation, student learning activities, student learning outcomes, and student responses. One teacher of class Va and all 31 pupils in class Va served as the study's subjects. Observation, tests, and questionnaires are the three methods of gathering data, and the tools utilized are observational or test questions, questionnaire sheets, and observational or observation sheets. The study's findings show that, with a percentage of 94%, the management of learning implementation is rated as